Serum IL-1 Β Levels İn Preeclamptics And Non-Preeclamptics Affected With Or Without Periodontitis: Serum IL-1 Β Levels in Preeclamptics and Non-Preeclamptics - Sadiqa, Ayesha; Majeed Cheema, Abdul (Pakistan Journal of Health Sciences, 2022)
Literature supported the association of bio-inflammatory cytokines in multifactorial pathologies such as preeclampsia and periodontitis. Objectives: To compare serum IL-1β in non-preeclamptic and preeclamptic pregnancies affected with/without periodontitis. Methods: Longitudinal cohort study was conducted on 73 pregnant women of Narowal (Pakistan) aged between 18-34 years, after seeking their consent. Wherein 33 subjects were periodontally healthy (6 preeclamptics, 27 non-preeclamptics) while 40 subjects were with periodontitis (6 preeclamptics, 34 non-preeclamptics). Serum samples were collected in antepartum and postpartum periods of the same subjects. Periodontium was examined by CPITN index, preeclampsia via blood pressure records. IL-1β was estimated through ELISA. Results: Raised IL-1β(pg/L) were observed in postpartum than antepartum i.e. 76% in non-preeclamptics with periodontitis(p=0.099), 89% in periodontally healthy non-preeclamptics(p=0.082), 313% in preeclamptics with periodontitis(p=0.242), and 34% in preeclamptics with healthy periodontium(p=0.351). Likewise, elevated IL-1β levels were found in non-preeclamptics than preeclamptics in antepartum and postpartum i.e. 327% in antepartum of periodontitis-affected non-preeclamptics(p=0.251), 0.43% in antepartum of periodontally healthy normotensives(p=0.983), 82% in postpartum of periodontitis affected non-preeclamptics(p=0.382), and 41% in postpartum of periodontally healthy non-preeclamptics(p=0.611). Similarly, high IL-1β levels were estimated in antepartum: 23% in non-preeclamptics with periodontitis than periodontally healthy non-preeclamptics(p=0.553) and 248% in periodontally healthy preeclamptics than periodontitis-affected preeclamptics(p=0.011). Also, increased IL-1β levels were noticed in postpartum: 15% in normotensives with periodontitis than periodontally healthy non-preeclamptics(p=0.694) and 12% in periodontally healthy preeclamptics than periodontitis-affected preeclamptics(p=0.853). Conclusion: Pregnancy suppressed IL-1β in preeclamptic and non-preeclamptics, while periodontitis without preeclampsia raised IL-1β in pregnancy and post-pregnancy phases.